Marketing Transformation Strategy in the Digital Era of the Bangkalan Geger Area - Mohammat Abdul Gofar (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2024)
In the ever-growing digital era, companies face new challenges and opportunities in the field of marketing. Digital marketing transformation has become important to remain competitive and relevant in the global market. This article discusses various effective marketing transformation strategies in the digital era, including the use of social media, search engine optimization (SEO), content marketing, and data analysis. Through case studies and literature analysis, it was found that the integration of digital technology not only improves operational efficiency but also allows companies to better understand and meet customer needs. The conclusion of this research shows that companies that are successful in digital marketing transformation are those that are able to adapt new technology, manage data effectively, and continuously innovate in their marketing approach. This article provides practical guidance for marketers to design and implement adaptive and sustainable digital strategies.